2016
DOI: 10.1017/s0954579416000973
|View full text |Cite
|
Sign up to set email alerts
|

The endocrinology of human caregiving and its intergenerational transmission

Abstract: Variation in the quality of parental care has a tremendous impact on a child's social-emotional development. Research investigating the predictors of this variability in human caregiving behavior has mostly focused on learning mechanisms. Evidence is currently accumulating for the complementary underlying role of steroid hormones and neuropeptides. An overview is provided of the hormones and neuropeptides relevant for human caregiving behavior. Then the developmental factors are described that stimulate variab… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
55
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 56 publications
(63 citation statements)
references
References 301 publications
(474 reference statements)
4
55
0
Order By: Relevance
“…measures. This may account for the fact that previous studies provided inconsistent findings in parental responsivity towards ingroup and outgroup infants (Esposito et al, 2014;Golle, Probst, Mast, & Lobmaier, 2015;Hodsoll, Quinn, & Hodsoll, 2010;Proverbio, De Gabrielle, Manfredi, & Adorni, 2011) and highlights the importance of incorporating neurobiological measures (see also Bos, 2016). Similarly, Senese and colleagues (2017) showed that implicit associations to infant faces were influenced by genetic polymorphisms and early care experiences.…”
Section: Discussionmentioning
confidence: 92%
“…measures. This may account for the fact that previous studies provided inconsistent findings in parental responsivity towards ingroup and outgroup infants (Esposito et al, 2014;Golle, Probst, Mast, & Lobmaier, 2015;Hodsoll, Quinn, & Hodsoll, 2010;Proverbio, De Gabrielle, Manfredi, & Adorni, 2011) and highlights the importance of incorporating neurobiological measures (see also Bos, 2016). Similarly, Senese and colleagues (2017) showed that implicit associations to infant faces were influenced by genetic polymorphisms and early care experiences.…”
Section: Discussionmentioning
confidence: 92%
“…Nonetheless, we did not explore the possibilities of other hormonal changes that could have a positive impact after an insult. Oestrogen and oxytocin levels change in sires . Using different lesion techniques, these hormones have been investigated as possible neuroprotective agents (oestrogen and oxytocinmediated neuroprotection).…”
Section: Discussionmentioning
confidence: 99%
“…Oestrogen and oxytocin levels change in sires. 38 Using different lesion techniques, these hormones have been investigated as possible neuroprotective agents (oestrogen 39,40 and oxytocin 33,41,42 mediated neuroprotection). As a result of the complexity of parental adaptations occurring in the male, more experiments are needed to address the possibility that these hormones, differentially regulated in sires, have a role in the neuroprotective effects observed in the present study.…”
Section: Interaction With the Pups And Dam But Not The Pregnant Femmentioning
confidence: 99%
“…Thus, sensory signals from their infants and partners, interactions with them, and cognitive and emotional processes related to that intensive stage of fathering may have neural effects that influence functions of the hypothalamus, yielding joint profiles of reduced T and elevated PRL. In single‐hormone approaches, both lower T and higher PRL have also been linked to greater paternal participation in caregiving and higher quality fathering behaviors (Bos, ; Gettler, ; Storey & Ziegler, ). In future studies involving these hormones and others, such as vasopressin, oxytocin, and cortisol, multi‐hormone perspectives can provide critical insights on the ways in which some constellations of hormonal function have synergistic, additive effects on expressions of sensitive, nurturing fathering while others (e.g.,) facilitate harsher practices (Bos, ).…”
Section: Discussionmentioning
confidence: 99%
“…To expand the richness of our understanding of these biosocial phenomena from evolutionary, psychobiological, and applied perspectives, there is a need to increase the breadth of physiological signals included in such studies, and to begin to move towards analytical perspectives and research designs that enable us to test how various hormones act together or in opposition to one another to produce divergent behavioral and health outcomes (Bos, ; Feldman, Gordon, Influs, Gutbir, & Ebstein, ; Gettler, , ; Storey & Ziegler, ; van Anders et al, ). Indeed, less is known about other hormonal signals that might be responsive to life history transitions and implicated in expressions of fathering, such as estradiol (E2).…”
Section: Introductionmentioning
confidence: 99%